Tropical response to stratospheric sudden warmings and its modulation by the QBO. Issue 12 (30th June 2014) - Gómez‐Escolar, M.; Calvo, N.; Barriopedro, D.; Fueglistaler, S.
Abstract Major Stratospheric Sudden Warmings (SSWs) are characterized by a reversal of the zonal mean zonal wind and an anomalous warming in the polar stratosphere that proceeds downward to the lower stratosphere. In the tropical stratosphere, a downward propagating cooling is observed. However, the strong modulation of tropical winds and temperatures by the quasi‐biennial oscillation (QBO) renders accurate characterization of the tropical response to SSWs challenging. A novel metric based on temperature variations relative to the central date of the SSW using ERA‐Interim data is presented. It filters most of the temperature structure related to the phase of the QBO and provides proper characterization of the SSW cooling amplitude and downward propagation tropical signal. Using this new metric, a large SSW‐related cooling is detected in the tropical upper stratosphere that occurs almost simultaneously with the polar cap warming. The tropical cooling weakens as it propagates downward, reaching the lower stratosphere in a few days. Substantial differences are found in the response to SSWs depending on the QBO phase. Similar to what is observed in the polar stratosphere, tropical SSW‐associated temperatures persist longer during the west QBO phase at levels above about 40 hPa, suggesting that the signal is mainly controlled by changes in the residual mean meridional circulation associated with SSWs. Conversely, in the lower stratosphere, around 50–70 hPa, enhanced cooling occurs only during QBO east phase. This behavior seems to be driven by anomalous subtropical wave breaking related to changes in the zero‐wind line position with the QBO phase.